Analysis and Policy Design of Street Vendors Management in Bandar Lampung - Sulistio, Eko Budi (UI Scholars Hub, 2013)
Street vendors (PKL) are common phenomena in urban areas all around the world, including in Indonesia. Bandar Lampung, as one of big cities in Indonesia, also has street vendor phenomenon. Some consider PKL illegal, yet some others perceive its existence as a way to overcome unemployment and poverty. Despite the different views, PKL is often considered as a source of urban problems by some regional governments in Indonesia, including Bandar Lampung Municipal Government. The research aims to analyze PKL phenomenon in Bandar Lampung and alternative policy issued to overcome PKL problems. The research result shows that the emergence of PKL in Bandar Lampung is caused by several factors, such as survival factor, lack of capital for running formal-sector business, reason of fulfilling educational needs, lack of employment, difficult bureaucracy, temporary job, lineages, and as a true profession. Based on the arguments and facts proposed, Bandar Lampung government must design a better policy to better accommodate PKL.